The role of CNC surface modification on the structural, thermal and electrical properties of poly(vinylidene fluoride) nanocomposites - Rincón-Iglesias, M. (2020)
This work shows the effect of cellulose nanocrystal surface charge on the morphology, structure, thermal and dielectric properties of poly(vinylidene fluoride) nanocomposites. CNCs extracted through sulfuric acid hydrolysis were modified using sodium hydroxide and cationization treatments to yield CNCs with zeta-potential values of − 26.1 ± 3.7 and − 4.4 ± 0.3 mV in comparison with the original highly-negative − 45.2 ± 1.1 mV. Nanocomposites where then obtained through doctor-blade casting followed by room temperature drying. CNC incorporation allows obtaining PVDF with 100% of γ-phase. An increase of the real dielectric constant ε′, dielectric loss tan δ and AC conductivity was observed by increasing CNC content. More importantly, these values are further boosted upon CNC surface-modification, suggesting the pivotal role of the CNC–PVDF interface. We conclude that the sulfate half-ester removal increase the amount of exposed –OH groups with increase the amount of accumulated charges at the PVDF–CNC interfaces.